Critical considerations and computational tools in plant genome editing - Dipnarayan Saha; Alok Kumar Panda; Subhojit Datta (Heliyon)
Recent advances in genome editing tools and CRISPR-Cas technologies have enabled plant genome engineering reach new heights. The current regulatory exemptions for certain categories of genome edited products, such as those derived from SDN-1 and SDN-2, which are free of any transgene, have significantly accelerated genome editing research in a number of agricultural crop plants in different countries. Although CRISPR-Cas technology is becoming increasingly popular, it is still important to carefully consider a number of factors before planning and carrying conducting CRISPR-Cas studies. To attempt genome editing in a plant, a high-quality genome sequence and a repeatable tissue culture protocol for in vitro regeneration are essential. One of the most important steps in plant genome editing is the designing of a CRISPR construct, which involves selecting the appropriate Cas protein, sgRNA sequence, and appropriate regulatory sequence to trigger expression. Computational tools and algorithms play a crucial role in construct design and gRNA selection to minimize off-target effects and also to optimize their delivery techniques. Researchers may need to select appropriate software tools capable of analyzing post-editing detection of mutation events and other DNA sequence abnormalities to identify off-target effects. To fully fulfill the potential of plant genome editing, continued advances in computational biology are essential to meet the challenges it faces today.